2021
DOI: 10.1136/bmjopen-2020-048204
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of a just-in-time adaptive intervention (JITAI) smoking cessation smartphone app: the Quit Sense feasibility trial protocol

Abstract: IntroductionA lapse (any smoking) early in a smoking cessation attempt is strongly associated with reduced success. A substantial proportion of lapses are due to urges to smoke triggered by situational cues. Currently, no available interventions proactively respond to such cues in real time. Quit Sense is a theory-guided just-in-time adaptive intervention smartphone app that uses a learning tool and smartphone sensing to provide in-the-moment tailored support to help smokers manage cue-induced urges to smoke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…A further six studies examined the use of smartphone sensing to detect intake and intoxication due to substances such as alcohol [ 60 , 61 , 62 ], tobacco [ 63 ], and cannabis [ 12 , 64 ]. They utilized location and activity data to understand the contexts of consumption and its impact on mobility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further six studies examined the use of smartphone sensing to detect intake and intoxication due to substances such as alcohol [ 60 , 61 , 62 ], tobacco [ 63 ], and cannabis [ 12 , 64 ]. They utilized location and activity data to understand the contexts of consumption and its impact on mobility.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cannabis intake would impact gait and reduce physical activity, which can be monitored through accelerometer [ 64 ] and location data [ 12 ]. This ability to detect intake instances was seen to provide useful opportunities for intervention using smartphones [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Costa et al have shown promising results for a wearable smartwatch to regulate emotions in the moment using vibrations that mimic one's heart rate [12]. In the context of smoking cessation, multiple studies are exploring ways to deliver CBT or mindfulness strategies in the moment when a person experiences a trigger or urge to smoke [9,11,20,24]. However, to our knowledge, no interventions have combined cognitive behavioral strategies with haptic methods of decreasing arousal in the moment of cuereactivity.…”
Section: Real-time Digital Interventions For Smoking Cessationmentioning
confidence: 99%
“…A systematic review of trials that compared a tailored and interactive Internet intervention to a non-active control demonstrated an effect in favour of the intervention [ 16 ], but none of these studies involved making a formal request for treatment using an online portal with direct linkage to general practice. There is already widespread availability of smartphone applications [ [20] , [21] , [22] , [23] ] and online support tools for smoking cessation [ 24 ] with demonstrable evidence of effectiveness of internet based interventions [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%